USVs as Challenges and Opportunities: The Urgency of Their Utilization in Indonesia’s Maritime Defense - Zahwa Aulia Nurul ‘Aini; Sabila Fajrin Achmadi; Keysha Valeriena Sachenka Whira Andini; Ivandra Solihin (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Indonesia is confronting increasingly complex maritime security challenges, particularly with the rise of non-traditional threats such as IUU fishing and recurring territorial violations. The limited surveillance infrastructure has heightened interest in USVs as a cost-efficient technology capable of enhancing detection, patrol, and defensive operations. Using a qualitative approach grounded in an extensive literature review, this study examines both the opportunities and the enduring constraints surrounding the integration of USVs into Indonesia’s maritime defence system. The findings indicate that USVs can substantially enhance monitoring capacity, improve personnel safety, and support the broader modernisation of national defence capabilities. However, significant challenges persist, including regulatory gaps, financial constraints, and emerging security risks linked to foreign USV activities. Overall, the study concludes that the strategic adoption of USVs backed by stronger domestic capacity and deeper international cooperation holds considerable potential for reinforcing Indonesia’s maritime security and sovereignty.